(untitled) (International Current Pharmaceutical Journal, 2013)
In the present study, the Allium cepa chromosome assay was employed as a preliminary test to investigate the mutagenic and antimutagenic potential of three plants, namely Clinacanthus nutans, Adhatoda vasica, and Carica papaya, used by traditional practitioners in Malaysia against a direct acting mutagen-Methyl Methanesulphonate (MMS). Onions were planted in various treatment groups: plant extract alone, treatment 1 (pre-treatment with MMS and transfer into plant extracts), and treatment 2 (mixture of MMS and plant extracts). The bulbs planted in the extract alone for cytotoxicity and mutagenicity assessment revealed that none of the extracts of the three plants except the 50 mg/kg of methanol extract of A. vasicawere cytotoxic to A. cepa cells, but a moderate level of mutagenicity was observed at 200 and 400 mg/kg of methanol extract of C. papaya and at 400 mg/kg of aqueous extract of C. nutans. Antimutagenic screening on the other hand revealed that all the extracts tested were able to reduce the percentage chromosomal aberration induced by MMS, both in treatment 1 and 2. Besides that, MMS-induced cell death was also observed to be reduced in onion root cells treated with the plant extracts. Therefore, taking all the results obtained into consideration, the order of the plant extracts with increasing suppressiveness against MMS was C. papaya < A. vasica < C. nutans. DOI: http://dx.doi.org/10.3329/icpj.v2i8.15588 International Current Pharmaceutical Journal, July 2013, 2(8): 131-140